Effects of Working Memory Capacity and Tasks in Processing L2 Complex Sentence: Evidence from Chinese-English Bilinguals - Zhou, Huixia; Rossi, Sonja; Chen, Baoguo (Frontiers in Psychology, 2017)
Two experiments aimed at investigating how working memory capacity related to processing wh-extractions in both a grammatical judgment and a translation task by using the Automated Operation Span task. A self-paced paradigm was used to collect response times and accuracy rates. In Experiment 1, results showed that high working memory capacity was related to faster grammatical judgment of the critical region in subject- and object-extractions. In Experiment 2, high working memory capacity was only related to high accuracy in translating wh-extractions. These results indicate that individual differences in working memory capacity play a certain role during L2 sentence processing, and experimental tasks can modulate this effect.